EXPERIMENTAL STUDY AND ANALYSIS OF POWER QUALITY ON HARMONIC MEASUREMENT - Athiya, Rashmi; Sharma, A.K. (International Journal of Research -GRANTHAALAYAH, 2020)
In this paper, we are study the measurement of harmonic distortion with the help of experimental approach in which included the various equipment and loads such as Experimental setup, Indicator, A.C. power supply, circuit with transformer, switch for different loads, different loads (Filament bulb, CFL and LED).